The Effect of PLEASE Strategy as Metacognitive Learning for Improving Vocational Students’ Writing Skill - Nike Angraini; Artika Wulandari (Arabic Language Education Study Program, Tarbiyah and Teacher Training, UIN Prof K.H Saifuddin Zuhri Purwokerto, 2026)
Writing is a crucial skill in learning English, yet many students, especially in vocational high school, still struggle to master it. One potential solution is the PLEASE strategy, a metacognitive technique that guides students through the writing process and helps them organize ideas effectively. This study investigated its impact on students’ writing. The aim was to find out whether the PLEASE strategy could significantly improve students’ writing skill. A quantitative method was used, involving 75 tenth-grade students of SMK Negeri 2 Palembang in the academic year 2024/2025. They were conveniently divided into two groups: X TKJ 1 as the control class with 38 students and X TKJ 2 as the experimental class with 37 students. The data were collected through essay writing tests on a report text over twelve meetings, including a pretest, treatments using the PLEASE strategy, a post-test, and a questionnaire. Results from the paired samples test showed a t (36) = -6.486 with p < 0.001, whereas the independent samples test yielded a t (73) = 2.489 with p = 0.015. These results indicate that the PLEASE strategy significantly improved students’ writing performance and can be considered an effective technique for teaching writing.